Depression and suicidal ideation in adolescents: a narrative review. - Tirado Chacaliaza, Karina Pamella (2022)
The objective of the following research was to identify the main findings regarding depression and suicide ideation in adolescent population, through a revision of narrative type, nine articles were analyzed, in which we were able to find the main characteristics of the variables mentioned, significant results were found between 2016 and 2021, these state that depression and suicide ideation have increased, being the highest rate in 2021, where 80 percent of adolescents have had at least once in their lives suicide ideation and the lowest rate was found in 2017, in which 30 percent showed suicide ideation and 9 percent depressive symptoms. Likewise, we can point out that these findings allow us to have a better outlook of depression and suicide ideation characteristics; which allow us to consider intervention measurements and establish preventive actions.